Efektivitas Kehadiran Bank Tanah terhadap Perlindungan Hukum Masyarakat Adat Atas Tanah Adat Studi Kasus di Kecamatan Medan Belawan - Andre Dwi Putra Sinaga; Hizkia Roland Prawyra Sitorus; Lennai Situmorang; Devi Sri Wahyuni; Putri Lopiga Br Tarigan; Naulita Panggabean; Parlaungan Gabriel Siahaan; Sri Hadiningrum (CV Rewang Rencang, 2024)
This research examines the effectiveness of the Land Bank in the legal protection of indigenous peoples over customary land in the Medan Belawan Sub-district. Using a qualitative approach and case study method, the research involved interviews and document analysis. Results show that the Land Bank is not involved in horizontal conflicts between indigenous peoples and companies, but focuses on vertical disputes between indigenous peoples and the government. Legal protection is provided by the National Land Agency (BPN) through land registration and recognition of customary land. The Land Bank manages no-man's land and acts as a conflict mediator to prevent misuse of Adat land.